Strategi Promosi Produk Dimsum Mentai untuk Meningkatkan Minat Beli Konsumen B2c: Studi Kasus Dimsum.Io - Reny Oftaviani Saragih; Mukdin Markus Turnip; Muhammad Roestian Fahmi Nasution (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
The lack of integrated promotional activities and reliance on short-term price promotion are the main challenges faced by dimsum.io in reaching new consumers. This highlights the need to identify appropriate promotional media and design effective promotional strategies to increase B2C consumer purchase interest in dimsum.io’s mentai dimsum products. This study employed a qualitative method with a descriptive approach. Data were collected through observation, questionnaires administered to respondents, and documentation including sales data, promotional content, and digital advertising results. Data analysis used the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The findings indicate that Instagram is effective in building consumer awareness and interest through visual content, while WhatsApp Business serves as a communication and ordering channel. However, both platforms have not been able to reach new consumers. Following the use of GrabAds, the number of transactions increased from 31 orders in December 2025 to 60 orders in January 2026, representing a growth of 93.5%. GrabFood’s contribution to total orders also rose from 6.5% to 21.7%. This study produced an integrated digital-based promotional strategy through strengthening Instagram content planning, optimizing WhatsApp Business as a follow-up and closing channel, and utilizing GrabFood as a new customer acquisition medium through Search Ads. This strategy forms a promotional loop that supports a long-term increase in consumer purchasing interest.